Strategi Kepala Sekolah Dalam Meningkatkan Mutu Pembelajaran di SDN 066043 Kecamatan Medan Helvetia Medan - Harlen Simanjuntak; Veryyon Harahap (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
The strategy adopted by the principal is the most decisive factor in the success of quality improvement at SDN 066043, Medan Helvetia District, Medan. The purpose of this study is to describe the principal's strategy of planning, implementing, monitoring and constraining. The study used a qualitative approach with descriptive methods. Data collection techniques used are Observation, Interview and Documentation Study. The research subjects were the Committee, Principal, Teachers and Students. The results showed: 1) Principal's strategy in planning to improve the quality of learning is to invite all school members and cooperate with committees, teachers and the community in order to improve the quality of education in schools 2) Principal's strategy in implementing improving the quality of learning is that teachers who Caring for all fields of study is already a professional path. 3) The principal's strategy in controlling quality improvement is that supervision is carried out in every aspect that is considered related to improving the quality of learning in schools. 4) The principal's strategy in terms of quality improvement barriers are: principals find it difficult to allocate time in improving the quality of learning in schools, then cannot control all activities to improve the quality of learning in schools.